A MAPK/miR-29 Axis Suppresses Melanoma by Targeting MAFG and MYBL2 - Vera, Olga (Cancers (Basel), 2021)
SIMPLE SUMMARY: The miR-29 family is subjected to complex regulation by tumor suppressors and oncogenes and has tumor suppressive potential in several cancers. We demonstrate that, in melanoma, oncogenic BRAF paradoxically induces miR-29 in concert with p53, thereby forming a barrier to melanoma progression. This barrier is overcome by reduced expression of miR-29, likely via diminished p53 activity. We further identify the transcription factors MAFG and MYBL2 as targets of miR-29 and show that their repression is detrimental for melanoma cells. Targeting MAFG- and MYBL2-regulated processes may therefore represent a promising therapeutic strategy to treat miR-29-low melanoma. ABSTRACT: The miR-29 family of microRNAs is encoded by two clusters, miR-29b1~a and miR-29b2~c, and is regulated by several oncogenic and tumor suppressive stimuli. While in vitro evidence suggests a tumor suppressor role for miR-29 in melanoma, the mechanisms underlying its deregulation and contribution to melanomagenesis have remained elusive. Using various in vitro systems, we show that oncogenic MAPK signaling paradoxically stimulates transcription of pri-miR-29b1~a and pri-miR-29b2~c, the latter in a p53-dependent manner. Expression analyses in melanocytes, melanoma cells, nevi, and primary melanoma revealed that pri-miR-29b2~c levels decrease during melanoma progression. Inactivation of miR-29 in vivo with a miRNA sponge in a rapid melanoma mouse model resulted in accelerated tumor development and decreased overall survival, verifying tumor suppressive potential of miR-29 in melanoma. Through integrated RNA sequencing, target prediction, and functional assays, we identified the transcription factors MAFG and MYBL2 as bona fide miR-29 targets in melanoma. Our findings suggest that attenuation of miR-29b2~c expression promotes melanoma development, at least in part, by derepressing MAFG and MYBL2.